Methodology for prediction of anticancer action of (2-oxo-2H-[1,2,4]¬triazino[2,3-c]-quinazolin-6-yl)thiones via QSAR and docking studies - I. S. Nosulenko; O. Yu. Voskoboynik; O. M. Antypenko; G. G. Berest; S. I. Kovalenko (Zaporožskij Medicinskij Žurnal)
Aimed to elaborate new group of protein kinase inhibitors we conducted receptor-based screening (docking, QSAR modeling) and biochemical testing for derivatives of (2-oxo-2H-[1,2,4]triazino[2,3-c]quinazolin-6-yl)thiones.